PTH-194 Palliative home parenteral nutrition (HPN) – tertiary gi oncology centre audit of practice. (22nd June 2015) - Charlesworth, AS; LeCouteur, J; Newall, S; White, R; O'Sullivan, S; Tocher, K; Ferreira, C; McCarthy, M; Dunn, JM
Abstract : Introduction: The European Society of Parenteral and Enteral Nutrition (ESPEN) guidelines state that "in intestinal failure (IF), long term PN should be offered if enteral nutrition is insufficient, expected survival due to tumour progression is longer than 2–3 months, it is expected that HPN can stabilise or improve performance status and quality of life and the patient desires this mode of nutrition support". This study aims to review current practice in the prescribing patterns of palliative HPN, following publication of the guidelines. Method: Retrospective casenote review of patients with cancer set up on HPN, between May 2011 and February 2015. GSTT is a tertiary GI oncology and regional IF centre. Results: There were 12 patients (10 male, 2 female) set up on HPN, and one on Home IV fluids, within the 45 months period. One patient died awaiting HPN but had received PN at his local hospital prior to transfer. The majority of patients had primary GI cancer (12/13). The median age was 51 years (range 26–70 years). The total length of HPN was 1323 days, with a catheter related blood stream infection rate of 0.8/1000 catheter days. The median length on HPN was 86 days (range 1–310 days). Mortality is 62%, with a median of 37 days HPN (range 0–111 days). Chemotherapy was administered concurrently with HPN in 62%. There has been an increase in patient numbers, with 4 started in the first 3 years, and a further 9 patients set up over the last 9 months. This indicates a growing awareness and utilisation of palliative TPN. Conclusion: The overall median length of HPN was 86 days, in keeping with the ESPEN guidelines of expected survival of longer than 60 days. We appear to be using HPN appropriately and are improving patient selection. There is anticipated increasing demand for HPN in the palliative setting, necessitating appropriate resource allocation regionally. Disclosure of interest: None Declared. Reference: Bozetti F, Arends J, Micklewright A, et al . ESPEN guidelines on parenteral nutrition: non-surgical oncology. Clin Nutr. 2009;28:445–454